INTERACTION BETWEEN POND-BOTTOM SOIL AND WATER QUALITIES - Mollah, M F A; Haque, A K M Aminul; Eaqub, M; Idris, M; Chaudhury, M Y (Indian Journal of Fisheries, 2011)
Considerable monthly variations were observed in soil properties and waterqualities of two ponds during a six-mo:ith period. The textural class of soil of.Pond 1 was silt loam and that of Pond 2, in general, silty day loam. The in-washof silt, etc., with the large volume of surface run-off of rain water from the surroundingagriculture farm, and the suspension of the dead self-vegetation of thepond, resulted in the lowest value of transparency in Pond 1 being recorded duringJuly; whereas, the relatively abundant growth of phyto-plankton in Pond 2 wasresponsible for reduced transparency there in May and again in August, as comparedwith the same in the remaining four months of the study period. The pH ofbottom soil and of water indicated that Poivd 2 is more suitable for fish culture